A comparison of the morphology and ultrastructure of the diatoms (Bacillariophyceae) Discostella stelligera and D. elentarii from two lakes in Fiordland, New Zealand - J.M. Knapp; P.C. Furey; R.L. Lowe (New Zealand Journal of Marine and Freshwater Research, 2006)
Morphological and ultrastructural variability of the diatoms, Discostella stelligera and Discostella elentarii, were examined from lakes Te Anau and Manapouri, located in Fiordland on the South Island of New Zealand. The objectives of this study were to examine and compare the size variability, frustule morphology, and ultrastructural detail of these taxa, which were recently collected from locations of a different origin than the type localities. To support the current descriptions of the newly erected genus of Discostella and recently described species, D. elentarii, information on morphological characteristics across valve patterns was compared. A principal components analysis of the external valve features of D. stelligera and D. elentarii measured by light microscopy did not separate the two taxa. This close similarity in external morphology highlights the need to optically dissect the valves underneath the light microscope to clearly differentiate between the convex/concave nature of the D. stelligera valves compared with the flat valve of D. elentarii. New external and internal morphological details of D. elentarii were documented with a field emission scanning electron microscope.